Masochism, Marginality, and the Metropolis: Kutlug Ataman's Lola and Billy the Kid - Barbara Mennel (Studies in 20th & 21st Century Literature, 2004)
Baltimore: "What you get is what you see" While sitting at the window of "City Café," a gay café in Baltimore, I let my eyes wander to the other side of the street where a group of young gay black men were camping it up…
Keywords: Masochism; Marginality; Metropolis; Kutlug Ataman; Lola and Billy the Kid; Film; crtitic; review; gay; gender